The Arabidopsis FRIENDLY (FMT) protein interacts with NAC and determines where nuclear-encoded mitochondrial proteins are translated - Valentina Montoya-Brach; Jeanne Roignant; Grégory Renard; Johana Chicher; Anne-Marie Duchêne (Proceedings of the National Academy of Sciences, 2026)
Mitochondria are not only the powerhouses of the cell. They are also dynamic signaling hubs, playing a key role in cellular metabolism and adaptation. Proper mitochondrial function depends largely on the import of proteins encoded by the nucleus. Using proximity labeling (TurboID), we show that Arabidopsis thaliana FRIENDLY (FMT) protein is in close proximity to several organellar-destined proteins, mostly mitochondrial, during their translation. Many of the corresponding mRNAs are immunoprecipitated with FMT. Remarkably, when FMT is absent, its target mRNAs lose their correct cellular localization. Our TurboID approach, associated with immunoprecipitations and confocal microscopy, also demonstrates the interaction between FMT and the Nascent polypeptide Associated Complex (NAC), a ribosome-associated platform involved in the maturation and sorting of nascent peptides. Taken together, these results suggest that FMT, through its interaction with NAC and the ribosome, is involved in the spatial regulation of translation in the cell.